2015
DOI: 10.1016/j.lwt.2015.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the viscosity profile obtained for dispersions containing different proportions of milk protein concentrate / whey protein concentrate during simulated conditions of thermal processing

Abstract: 17Denaturation and interaction of different proteins occur in different forms and intensity 18 when the pH value varies in accordance with the medium in which they are located. 19This study aimed to verify the influence of whey protein/casein interaction in the 20 evolution of viscosity at different pH values, using the Rapid Viscosity Analyzer (RVA) 21 as the thermal processing simulator. Samples of commercial whey protein concentrate 22 (WPC) and milk protein concentrate (MPC) have been analyzed. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Heating milk proteins at high temperature causes irreversible protein denaturation leading to aggregation and increases in concentrate viscosity (Anema et al, 2014;Souza et al, 2015). In this study, the increase rate of viscosity was assumed to be a linear response to the rate of protein denaturation.…”
Section: Modelling Viscosity Increase During Heat Treatment By Reactimentioning
confidence: 99%
See 1 more Smart Citation
“…Heating milk proteins at high temperature causes irreversible protein denaturation leading to aggregation and increases in concentrate viscosity (Anema et al, 2014;Souza et al, 2015). In this study, the increase rate of viscosity was assumed to be a linear response to the rate of protein denaturation.…”
Section: Modelling Viscosity Increase During Heat Treatment By Reactimentioning
confidence: 99%
“…Many previous studies have shown the significant effect of heat treatment temperature on whey protein denaturation (Anema et al, 2004;Anema and McKenna, 1996;Buggy et al, 2017;Kehoe et al, 2011;Oldfield et al, 2005;Oldfield et al, 1998) and subsequently viscosity of the concentrates such as skim concentrate (Anema et al, 2014) or concentrates containing different proportions of MPC and whey protein concentrate (Souza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Casein micelle size distribution, chymosin coagulation, and thermal stability are normally recovered by milk reconstitution after drying. However, this protein may undergo chemical and structural changes during the milk heating process, which may affect the profile of bioactive peptides produced during protein digestion (Souza et al, 2015).…”
Section: The Effect Of Heat Treatment On Macronutrientsmentioning
confidence: 99%
“…These associations modify the micellar surface, leading to an alteration of hydrophobicity and functionality of the reconstituted dairy products. Also, as a result of this aggregation, most proteins lose their biological activity, eventually promoting protein coagulation (Souza et al, 2015;Raikos, 2010;Borad et al, 2017;Qian et al, 2017). Also, a few of whey proteins, especially β-lactoglobulin, bind covalently to membrane proteins of fat globules (Liu et al, 2012).…”
Section: The Effect Of Heat Treatment On Macronutrientsmentioning
confidence: 99%
“…The concentration operation strongly modifies the product's physicochemical conditions, negatively impacting the concentrate as well as the process (Tanguy et al, 2016). Lactose crystallization, Maillard reaction, and increase in viscosity are consequences of the heating and of the concentration of the solids accompanying the milk evaporation (Arena et al, 2017;Stephani et al, 2015;Silva et al, 2015;Souza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%